Bridging the Gender Gap in Agribusiness Finance: Financial Inclusion Strategies and Their Effects on Women-Owned Enterprise Performance in Adamawa State, Nigeria: Financial Inclusion Strategies and Their Effects on Women-Owned Enterprise Performance in Adamawa State, Nigeria - Freda Ijanada Fidelis (AMAR (Andalas Management Review), 2026)
The study investigates the impact of financial inclusion on performance among women-owned agribusinesses in Adamawa State, Nigeria, using access, usage, and financial literacy as explanatory variables. Primary data was collected from 308 female NIWAB members of which 300 valid cases on multiple regression analysis applied. Access of finance (β = 0.330, p < 0.001) as well as use (β = 0.204, p < 0.01) of financial services was significantly increasing the performance of agribusiness but financial literacy (β = 0.050, p > 0.05) has negligible direct effect. It was observed through the findings the potential for available, relevant, flexible financial product in facilitating rural women's enterprise. The study extends Financial Intermediation Theory beyond its previous application only to male taxpayers in OECD countries by falsifying the hypothesis that finance awareness directly improves performance. Policy applications involve increasing access as well as utilization of financial services, in turn reconceptualizing financial literacy programs to align with agribusiness on-the-ground circumstances. The study extends Financial Intermediation Theory into the gendered agribusiness context and provides policy insights for integrating women into Nigeria’s rural financial ecosystem